Drug Utilization Evaluation of Antibiotics in Burn Patients at a Referral Teaching Hospital - Rasool Soltani; Shabnam Sajjadi; Kiana Shirani; Mohsen Minaiyan; Fatemeh Saghafi (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: Nowadays, due to the irrational and excessive use of antibiotics, antimicrobial resistance has become one of the main concerns of the medical community. Patients with burns are more prone to infections due to the loss of the skin's defense barrier and a weakened immune system. Therefore, proper antibiotic treatment is essential in these patients. In the present study, the rational use of antibiotics in the burn hospital of Imam Mousa Kazem in Isfahan was evaluated. Methods: This prospective cross-sectional descriptive study was performed on 102 hospitalized patients over 9 months (from January to September 2020). Adult burn patients who received at least one antibiotic were included in the study. All required information, including demographic data, the prescribed antibiotic, basis of administration (empiric vs. culture-based), dose and duration of use, microbial culture test, and treatment outcome were recorded in the data collection form by referring to patients' medical profile and the hospital computer system. Judgments about the accuracy of the indication, dose, and duration of treatment, as well as the need for dose adjustment in renal or hepatic impairment were made using related guidelines and references. Results: Among the 196 antibiotic prescriptions, cefepime (40.3%) was the most frequently used antibiotic, followed by vancomycin (17.9%) and meropenem (16.8%). Most prescriptions were empirical, while the antibiotics were administered based on the microbial culture results only in two cases (1.9%). The indication of use was correct in 52.6% of prescriptions (n = 103), of which 74.8% (n = 77) had correct dose. In addition, in 47 cases (45.6%), the duration of antibiotic therapy was correct. 6.8% of the patients died, 10.75 discharged with the patient's personal consent, and the rest of the them discharged in good condition. Conclusion: Prescribing antibiotics in Imam Moussa Kazem Hospital is associated with many errors in various aspects, including indication, dose, de-escalation, and duration of treatment.